Cost-effective baby corn (Zea mays) cultivation under drip fertigation - KUMAR, MUKESH; RAJPUT, T B S; PATEL, NEELAM (The Indian Journal of Agricultural Sciences, 2014)
Field experiment was conducted during 2010-2011 at the research farm of Water Technology Centre, Indian Agricultural Research Institute, New Delhi, India to study the economic viability of baby corn (Zea mays L.) cultivation round the year (October-February, April-July and August-November) under fertigation system. The present study consisted of nine treatments which includes three fertigation frequencies (biweekly, weekly and fortnightly) and three dripper 0.5, 1.0 and 1.5 kg/cm2 system operating pressures. Yield attributes of baby corn were significantly (P<0.05) affected by fertigation frequencies. Highest yield of cob, corn and fodder were recorded in biweekly fertigation schedule with dripper discharge at system operating pressure of 1.0 kg/cm2 (132.5, 22.5, 633.3 q/ha) during 2nd season however, lowest yields of cob, corn and fodder (65.8, 11.2 and 454.6 q/ha) were recorded under fortnightly fertigation schedule with dripper discharge at system operating pressure of 1.5 kg/cm2 during 3rd season. High values of benefit cost ratio (3.63) under biweekly fertigation during 2nd season and low values of benefit cost ratio (1.47) were found under fortnightly fertigation during 3rd season.